Preparation of nanocomposite aromatic polyamide reverse osmosis membranes by in-situ polymerization of bis(triethoxysilyl)ethane (BTESE) - Zheng, Feng-Tao; Qu, Jianbo; Sun, Zhou (Journal of membrane science, 2022)
Bis(triethoxysilyl)ethane (BTESE) nanoparticles were incorporated into aromatic polyamide (PA) membranes via in-situ polymerization to prepare BTESE nanocomposite PA (BTESE-TFN) membranes for reverse osmosis. In-situ polymerization was utilized to produce BTESE nanoparticles with high dispersion in PA membranes by adding BTESE as precursors into PA membranes for in-situ polymerization. Organic bridged -C-C- in BTESE provided enhanced compatibility between BTESE nanoparticles and PA membranes. The BTESE-TFN membranes showed durability with stable RO performance for more than 96 h because of the high dispersion of BTESE nanoparticles and enhanced compatibility between BTESE nanoparticles and PA membranes. The BTESE nanoparticles increased surface roughness, thickness, hydrophilicity of PA membranes. The BTESE nanoparticles changed surfaces of PA membranes to looser structure with more pores and gaps. However, low loadings of BTESE nanoparticles in the BTESE-TFN membranes were observed due to low reactivity of Si-OC2H5 groups in BTESE. Even so, salt rejection of prepared TFN-0.12 membrane was slightly improved to 96.81%, compared with that of prepared pristine PA membrane. The TFN-0.12 membrane showed water flux of 1.6 L/(m2•h•bar), 25% higher than the water flux of pristine PA membrane because of enlargement of pore sizes in BTESE nanoparticles, formation of a loose and rough membrane surface and enhancement of hydrophilicity of the membrane surface. Furthermore, modification of organic bridged groups in the BTESE exhibited great potential to further optimize the water flux and durability of BTESE-TFN membranes. [Display omitted] •Bis(triethoxysilyl)ethane nanocomposite aromatic polyamide membranes were prepared.•In-situ polymerization provided better dispersion of nanoparticles and durability.•Nanocomposite membranes showed 25% higher water flux than PA membranes.•Nanoparticles increased thickness, surface roughness, hydrophilicity of membranes.